2020
DOI: 10.3390/biom10050699
|View full text |Cite
|
Sign up to set email alerts
|

The Antitumor Agent Ansamitocin P-3 Binds to Cell Division Protein FtsZ in Actinosynnema pretiosum

Abstract: Ansamitocin P-3 (AP-3) is an important antitumor agent. The antitumor activity of AP-3 is a result of its affinity towards β-tubulin in eukaryotic cells. In this study, in order to improve AP-3 production, the reason for severe growth inhibition of the AP-3 producing strain Actinosynnema pretiosum WXR-24 under high concentrations of exogenous AP-3 was investigated. The cell division protein FtsZ, which is the analogue of β-tubulin in bacteria, was discovered to be the AP-3 target through structural comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…The results showed that the overexpression of ssgA _ 6663 did not improve AP-3 production, which was consistent with what was observed in S. griseus [ 26 , 28 ]. As expected, enhanced expression of ftsZ_5883 improved strain resistance against AP-3 [ 45 ], alleviated cell toxicity, and increased AP-3 production by 45% ( Figure 3 A). Moreover, overexpression of adpA_1075 increased AP-3 production by 85% without affecting dry cell weight (DCW) at the end of fermentation ( Figure 3 A,B).…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…The results showed that the overexpression of ssgA _ 6663 did not improve AP-3 production, which was consistent with what was observed in S. griseus [ 26 , 28 ]. As expected, enhanced expression of ftsZ_5883 improved strain resistance against AP-3 [ 45 ], alleviated cell toxicity, and increased AP-3 production by 45% ( Figure 3 A). Moreover, overexpression of adpA_1075 increased AP-3 production by 85% without affecting dry cell weight (DCW) at the end of fermentation ( Figure 3 A,B).…”
Section: Resultssupporting
confidence: 77%
“…Overexpression of ftsZ gene might also be used to alleviate AP-3 toxicity and improve resistance of A. pretiosum to AP-3. Since FtsZ was determined to be the intracellular binding target of AP-3 [ 45 ]. A high transcriptional level of ftsZ_5883 was observed in mutant with a denser mycelial interweaving pattern ( Figure 1 D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, a minimum of 27% increase in AP-3 yield was obtained based on the objectiveoriented strategies. The AP-3 production obtained in mutant MD02 (365 mg/L) was higher than those recently reported, where improvement of AP-3 tolerance and enhancement of the efflux efficiency of AP-3 were mainly focused (Wu et al 2020;Wang et al 2021Wang et al , 2020b. We additionally constructed the strain with both the knockout of gene cluster T1PKS-15 and the knock-in of BDP promoter.…”
Section: Discussionmentioning
confidence: 88%
“…The study by X. Wang et al [2] reveals that the antitumor agent named ansamitocin P-3 (AP-3) binds to cell division protein FtsZ in Actinosynnema pretiosum, a rare actinomycete. FtsZ, a β-tubulin analog present in bacteria, was discovered to be the AP-3 target through structural comparison and an Surface Plasmon Resonance (SPR) biosensor assay.…”
mentioning
confidence: 99%